2010
DOI: 10.1063/1.3450302
|View full text |Cite
|
Sign up to set email alerts
|

Thermostating highly confined fluids

Abstract: In this work we show how different use of thermostating devices and modeling of walls influence the mechanical and dynamical properties of confined nanofluids. We consider a two dimensional fluid undergoing Couette flow using nonequilibrium molecular dynamics simulations. Because the system is highly inhomogeneous, the density shows strong fluctuations across the channel. We compare the dynamics produced by applying a thermostating device directly to the fluid with that obtained when the wall is thermostated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
101
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(103 citation statements)
references
References 42 publications
2
101
0
Order By: Relevance
“…[37][38][39][40] The velocities in the flexible tubes are significantly higher than those in the rigid tubes, which can be due to several reasons as follows: (i) The vibration of wall atoms about their lattice sites smoothens the potential energy surface felt by the water molecules on the wall surface. (ii) Fluid molecules can slip past the flexible wall more favorably than past the rigid wall, since the flexible atoms can move backward due to steric repulsion to facilitate the flow, while the rigid wall atoms lead to specular reflection which slows down the flow, 18 as schematically depicted in Fig. 2. (iii) Momentum transfer from the excited phonon modes of the CNTs to the fluid has been suggested to contribute to the larger flow rates of water in flexible CNTs.…”
Section: A Thermostatting Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…[37][38][39][40] The velocities in the flexible tubes are significantly higher than those in the rigid tubes, which can be due to several reasons as follows: (i) The vibration of wall atoms about their lattice sites smoothens the potential energy surface felt by the water molecules on the wall surface. (ii) Fluid molecules can slip past the flexible wall more favorably than past the rigid wall, since the flexible atoms can move backward due to steric repulsion to facilitate the flow, while the rigid wall atoms lead to specular reflection which slows down the flow, 18 as schematically depicted in Fig. 2. (iii) Momentum transfer from the excited phonon modes of the CNTs to the fluid has been suggested to contribute to the larger flow rates of water in flexible CNTs.…”
Section: A Thermostatting Approachmentioning
confidence: 99%
“…16 A study on polymer melts sheared by Lennard-Jones walls found that the slip length increased with the shear rate when the walls were kept rigid, while the slip length was independent of the shear rate for flexible walls. 17 Bernardi et al 18 observed significant differences in temperature, density, velocity, and stress profiles between the two thermostatting approaches (i.e., flexible or rigid walls) and advocated thermostatting walls and caution in interpreting the slip obtained from NEMD simulations. Yong and Zhang 19 simulated the Couette flow of a Lennard-Jones fluid by thermostatting only the fluid, only the walls, or both, and they compared different thermostatting algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[51][52][53] Thermostatting the wall atoms rather than the confined sample is the most physically realistic option. The implementation of bulk system thermostats without modification may lead to spurious particle dynamics.…”
Section: Thermostattingmentioning
confidence: 99%
“…The temperature is maintained at T = 292.8 K by coupling molecules to a velocity-unbiased Berendsen thermostat (Berendsen et al 1984) with a time constant of s T ¼ 21:6 fs, applied within 36 independent bins placed in the y-direction, with each bin being 0.34 nm thick. It has been shown that using a thermostat on a confined fluid may affect the flow properties (Bernardi et al 2010); however, a thermostat is used in all the MD simulations in this work so that we can compare with isothermal CFD simulations. The same thermostat is used in both the pre-simulations and the full MD simulations; therefore, the same error is present in both-the verification of the simulation approach is thus not undermined by any physical uncertainty introduced by the thermostat.…”
Section: Pre-simulation Resultsmentioning
confidence: 99%